Livelihood Vulnerability Index and Adaptive Capacity of Smallholder Rice Farmer Households to Climate Change in the Manyaran District, Wonogiri Regency - Nissa', Zulfa Nur Auliatun (LPPM Universitas Trunojoyo Madura, 2025)
Agricultural production is vital for income and food security in rural areas. However, in Manyaran District, Wonogiri Regency's rice farming livelihoods are increasingly threatened by climate change, environmental pressures, and policy shifts. This study evaluates the vulnerability of rice farmers' livelihoods using the Livelihood Vulnerability Index (LVI) and the LVI-IPCC framework. Data were gathered from 42 randomly selected households in seven villages, revealing an LVI score of 0.61 and an LVI-IPCC score of 0.04, indicating medium vulnerability to climate change. Key factors contributing to livelihood vulnerability include exposure to droughts, floods, pests, rising rice production costs, and climate variability. Adaptations include strong social networks, technological innovations like simple irrigation systems, and ecological adjustments like crop diversification with alternative and horticultural crops. The study recommends that the government enhance support for farmers in downstream areas by improving irrigation infrastructure, increasing reservoirs and wells, and providing training for developing home-based food industries. These measures are intended to bolster resilience and adaptation in agricultural livelihoods amidst environmental and policy challenges.